PERAN GLUKOMANAN-ARANG AKTIF SEBAGAI HIPOKOLESTEROLEMIK PADA TIKUS SPRAGUE DAWLEY - Agus Malik Ibrahim; Irma Herawati Suparto; Tetty Kemala; Gustan Pari (Jurnal Penelitian Hasil Hutan, 2016)
Cholesterol is a metabolite which contains sterol fat, which is important to support cell functions and generate vitamin D, cortisol and reproduction hormones. Higher cholesterol content known as hypercholesterolemia is a predisposing towards cardiovascular disease. Previous study reported that glucommanan and activated charcoal individually can lower cholesterol levels, however combination both of them for lowering the cholesterol level has not been studied intensively. This paper examines the ability of glucommannan derived from Amorphophallus flour and activated charcoal in reducing cholesterol level of Sprague Dawley rat. Firstly, glucommanan was isolated from Amorphophallus flour and activated charcoal was produced from teak sawdust and coconut fiber. Both component were formulated and characterized using Fourier Transform Infra Red (FTIR), x-ray diffractometer and scanning electron microscope. Thirty five adult male Sprague Dawley rat with body weight of 160 to 200 g were divided into seven treatment groups: high-fat diet (DTL) and glucommanan, DTL and teak's activated charcoal (TC), DTL and cocout fiber's activated charcoal (CC), DTL and glucommanan and CC (1:1), DTL and glucommanan and CC (2:1), DTL and glucommanan and CC (1:2) and DTL without treatment as control. Initial rat cholesterol level was measured and it was compared with those after five weeks. Results show that the greatest cholesterol reduction (37.4%) is recorded from rat with DTL and glucommanan and CC (1:1) and low density lipoprotein reduction by about 49.7% and triglyceride reduction by 18.3%.